Fluorine-doped micropore-covered mesoporous carbon nanofibers for long-lasting anode-free sodium metal batteries - Haolin Zhu; Linfeng Peng; Junxiu Wu; Siwu Li; Qiang Wu; Shijie Cheng; Jia Xie; Jun Lu (Nature Communications)
Abstract Anode-free sodium metal batteries have gained significant attention due to the abundance of their material resources and high energy densities. However, their practical application is hindered by continuous sodium consumption and dendrite growth characteristics. In this study, we present fluorine-doped micropore-covered mesoporous carbon fibers to enhance the cycling performance of anode-free sodium metal batteries. The introduction of electronegative fluorine generates more Lewis acid sites and sodiophilic Zn-Nx sites, thereby suppressing electrolyte decomposition and promoting uniform sodium metal deposition. Structural modifications are implemented to create a micropore-covered mesoporous framework, resulting in the formation of a thin, uniform solid electrolyte interphase that facilitates Na metal confinement and self-smoothing. The carbon fibers as the current collector exhibit a low sodium nucleation overpotential and rapid sodium thermal infusion, demonstrating highly reversible sodium plating/stripping for more than 5000 cycles with an average Coulombic efficiency of 99.93% at a high current density of 5 mA cm−2. Furthermore, anode-free pouch cell with high-loading positive electrode achieves stable cycling characteristics for 200 cycles with 90% capacity retention. These findings demonstrate the efficacy of tailoring the compositions and microstructures of porous carbon current collectors for enhancing the cycling life and stability characteristics of sodium metal batteries.